1977
DOI: 10.2136/sssaj1977.03615995004100030037x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Versatile Experimental System for Soil Erosion Studies

Abstract: A laboratory facility for the study of soil erosion is described. Rainfall from a modular system supplied raindrops at near terminal velocity to prepared soil beds set in a flume with slope adjustable up to 30%. A comparison was made of erosion under overland flow alone and storm rains of the same intensity (discharge), but different energy levels. Raindrop impact in runoff flow was a powerful agency in promoting soil transport and inhibiting rill formation. Bed‐load movement was important in the transport of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…(as well as rainfall-driven) erosion sediment is enriched with finer particles at early times (e.g. Walker et al, 1977Walker et al, , 1978Moss et al, 1979;Alberts et al, 1980Alberts et al, , 1983Proffitt and Rose, 1991). These experimental observations are interpreted by theory , which shows that when the erosion processes are dominated by suspension and saltation, and if soil entrainment and re-entrainment processes are assumed to be non-selective with respect to size class, then this initial fine nature of sediment is predicted to occur.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…(as well as rainfall-driven) erosion sediment is enriched with finer particles at early times (e.g. Walker et al, 1977Walker et al, , 1978Moss et al, 1979;Alberts et al, 1980Alberts et al, , 1983Proffitt and Rose, 1991). These experimental observations are interpreted by theory , which shows that when the erosion processes are dominated by suspension and saltation, and if soil entrainment and re-entrainment processes are assumed to be non-selective with respect to size class, then this initial fine nature of sediment is predicted to occur.…”
Section: Discussionmentioning
confidence: 82%
“…1016/j.jhydrol.2007.05.019 size class dominating the eroded sediment (Meyer et al, 1980;Loch and Donnollan, 1982). At the steady state condition, many researchers (Walker et al, 1977(Walker et al, , 1978Moss et al, 1979;Govers, 1985;Palis et al, 1990;Proffitt and Rose, 1991;Rose, 1991, 1992a,b;Beuselinck et al, 1999;Hogarth et al, 2004) have found that size distribution of the sediment is very similar to that of the original soil.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements presented here show that flow velocity and raindrop impact, which are the main agents responsible for particle detachment and transport (Walker et al, 1977;Huang, 1995) ). The short length of the 1 m 2 plots does not allow flow velocity to increase sufficiently to reveal a slope effect.…”
Section: Sediment Concentrationmentioning
confidence: 78%
“…Therefore, modeling soil erosion based on rainfall intensity and inflow rate is necessary to evaluate the effects of rainfall and inflow on Mollisol hillslope soil erosion. Walker et al (1977) noted that the sediment transport rate under rainfall intensity was 5.0 times higher than that under the same equivalent inflow rate. Guy et al (1987) proposed that rainfall and runoff resulted in 85 and 15 % of sediment transport capacity, respectively.…”
mentioning
confidence: 95%